miR-149-3p Regulates the Switch between Adipogenic and Osteogenic Differentiation of BMSCs by Targeting FTO - Yuan Li; Fan Yang; Manqi Gao; Rui Gong; Mengyu Jin; Tianyi Liu; Yi Sun; Yutuo Fu; Qi Huang; Wenwen Zhang; Shenzhen Liu; Meixi Yu; et al. (Elsevier, 2019)
Bone marrow-derived mesenchymal stem cells (BMSCs) have been suggested to possess the capacity to differentiate into different cell lineages. Maintaining a balanced stem cell differentiation program is crucial to the bone microenvironment and bone development. MicroRNAs (miRNAs) have played a critical role in regulating the differentiation of BMSCs into particular lineage. However, the role of miR-149-3p in the adipogenic and osteogenic differentiation of BMSCs has not been extensively discovered. In this study, we aimed to detect the expression levels of miR-149-3p during the differentiation of BMSCs and investigate whether miR-149-3p participated in the lineage choice of BMSCs or not. Compared with mimic-negative control (NC), miR-149-3p mimic decreased the adipogenic differentiation potential of BMSCs and increased the osteogenic differentiation potential. Further analysis revealed that overexpression of miR-149-3p repressed the expression of fat mass and obesity-associated (FTO) gene through binding to the 3ʹ UTR of the FTO mRNA. Also, the role of miR-149-3p mimic in inhibiting adipogenic lineage differentiation and potentiating osteogenic lineage differentiation was mainly through targeting FTO, which also played an important role in regulating body weight and fat mass. In addition, BMSCs treated with miR-149-3p anti-miRNA oligonucleotide (AMO) exhibited higher potential to differentiate into adipocytes and lower tendency to differentiate into osteoblasts compared with BMSCs transfected with NC. In summary, our results detected the effects of miR-149-3p in cell fate specification of BMSCs and revealed that miR-149-3p inhibited the adipogenic differentiation of BMSCs via a miR-149-3p/FTO regulatory axis. This study provided cellular and molecular insights into the observation that miR-149-3p was a prospective candidate gene for BMSC-based bone tissue engineering in treating osteoporosis. Keywords: miRNA, osteoporosis, osteogenesis, adipogenesis, BMSC, differentiation, FTO